PENGARUH BAGI HASIL, PRODUK, DAN KUALITAS PELAYANAN, TERHADAP MINAT MENABUNG DI BANK SYARIAH (Studi Kasus pada Nasabah Bank Syariah Indonesia KCP UNGARAN) - Susetyarsi, Th.; Heridiansyah, Jefri; Wibowo, Purnomo Ari (STIE PENA, 2022)
The goal of this study is to see how much profit sharing, product , and service quality affect interest in saving in Islamic banks. A total of 100 customers from the Indonesian Islamic bank KCP Ungaran were employed in the study. Purposive sampling was used in this investigation, and the data used were primary data kinds. SPSS 22 was used to process the data in this investigation (IBM Statistical Package for Social Science). Profit sharing has a good but not significant effect on saving interest in Indonesian Islamic bank clients at KCP Ungaran, according to the findings of this study. This study also demonstrates the positive impact of Indonesian Islamic bank products on client savings motivation. Furthermore, this research demonstrates that service quality has a positive and significant impact.Keywords: Profit Sharing,Product,Service Quality, Interest in Saving